Performance of confined sheep fed diets based on silages of different sorghum cultivars - PINHO,Ricardo Martins Araujo (2017)
SUMMARY The aim of this study was to evaluate the use of silages of different sorghum cultivars through digestibility and nutrient intake and performance of sheep. The experiment was conducted at the Pendência Experimental Station, of the State Company for Agricultural Research of Paraíba S.A. For the experiment, thirty-five rams were used, without defined breed, with average live weight of 17.7 kg, distributed in a completely randomized block design, with five diets and seven replicates to determine intake and performance; and 25 non-castrated rams, without defined breed, distributed in a completely randomized design with five diets and five replicates, to determine the digestibility of nutrients. The average daily intake of dry matter was, on average, 994.66 g. Only the average intakes of ether extract, neutral detergent fiber and non-fibrous carbohydrates, were affected by the diets. The weight gain (WG), feed conversion and feed efficiency of the animals receiving the diets suffered no effect. Silages of BRS 655, 610, 800, 810 and Ponta Negra provided similar intake and digestibility of nutrients. The use of silages of different sorghum cultivars (BRS 610, BRS 655, BRS 800, BRS 810 and Ponta Negra) in diets for confined sheep provide similar performance and intakes.